Taking the lead? Transatlantic attitudes towards lethal drone strikes. (3rd July 2018) - Ceccoli, Stephen; Bing, John
Abstract : While opinion polls indicate majorities of Americans support the use of lethal drone strikes for counterterrorism purposes, European publics generally are much less supportive. This article develops and tests several individual-level explanations for such attitudes among survey respondents in the United States and seven European countries, including six European 'drone club' member states. Evidence suggests that ideology and core policy beliefs shape respondent sentiment in clear and convincing ways. Moreover, preferences for the closeness of the European-American security partnership and the relevance of NATO indicate the importance of a shared transatlantic identity as additional determinants.